The Relationship of Duration of Hemodialysis with Coping Mechanisms of Chronic Kidney Disease Patients Underwent Hemodialysis - Dewayani, I Gusti Agung Tirta; Lisnawati, Ketut; Purwanti, Ika Setya (Future Science, 2022)
Chronic Kidney Disease patients undergoing hemodialysis can cause stress to the patient. The longer the patient suffers from Chronic Kidney Disease, the more the patient has a variety of experiences with stressors due to the disease. These experiences can be used as an anticipatory effort in dealing with stressors experienced by patients. The purpose of this was the relationship between the duration of hemodialysis and the coping mechanism of patients with chronic kidney disease undergoing hemodialysis. This study used descriptive quantitative, with a correlation design and a cross-sectional approach. The sample was 111 patients with chronic kidney disease undergoing hemodialysis. Sampling technique used the purposive sampling technique. The data collection instrument used a jalowiec coping scale questionnaire and length of underwent hemodialysis. The results showed that most respondents underwent hemodialysis in the category <8 months (70.3%). The coping mechanisms in most patients were categorized as adaptive (55%). It was concluded that there was a relationship between the duration of hemodialysis and the coping mechanism in patients with chronic kidney disease undergoing hemodialysis (p = 0,000). The correlation strength value is 0.402 (moderate strength), and the direction of the correlation is negative, it shows that if the length of time is more than eight months, then the patient's coping mechanism becomes adaptive. The patient has accepted the situation he was undergoing, which is due to routine hemodialysis, which causes the patient to often meet other patients with the same problem so that by often telling each other they can share experiences and problems and encourage each other.